Functional bracing is a safe and cost effective treatment for isolated Weber B fracture. (December 2021) - Abdelaal, Ahmed; Elnikety, Sherif
Highlights: Functional bracing is cost effective in treatment of stable isolated Weber B fracture. Load bearing radiograph are the best to check stability in ankle fractures. Higher complications rate with cast immobilisation compared to functional bracing. Abstract: Background: Despite the current recommendations that stable Weber B ankle fractures can be treated with functional bracing and weightbearing as tolerated, some reluctance exists among trauma surgeons to follow these recommendations. This paper reports on our institution's experience in managing these injuries and compare it to the national guidelines. Patients and methods: This is a retrospective cohort study. Consecutive patients with isolated Weber B fractures referred to the local outpatient clinic over the period of six months were included in the study. Radiographs and clinic letters were examined, the patients were interviewed via telephone to obtain outcome scores [Olerud and Molander score]. Method of immobilisation, weight-bearing status, radiological fracture union, clinical outcomes and complications were all assessed and analysed. Results: One hundred and twenty-three patients with isolated Weber B fractures were identified. This cohort of patients did not show clinical or radiographic evidence of instability, they were deemed stable and were initially treated non-operatively. Minimum follow-up period was six months. Sixty-two patients were treated in plaster and were non-weight bearing on the affected limb, while 61 were treated with functional bracing in a boot and were allowed early weight bearing. Three patients showed displacement requiring surgical fixation. All fractures progressed to union and patients were discharged irrespective of the method of immobilisation or weightbearing status during treatment. There was no statistically significant difference in the functional outcome measures between the two groups. The protocol of functional bracing and weightbearing was associated with fewer outpatient clinics and a reduced number of radiographs obtained in the clinic and fewer complications. Conclusion: Isolated trans-syndesmotic Weber B ankle fractures, that are clinically and radiologically stable, can be safely treated with functional bracing in a boot and weightbearing as tolerated.